Yuen Woo Ping's WING CHUN - Vojković, Saša (New Hong Kong cinema., 2009)
Yuen Woo Ping's kung fu comedy based on the legendary female character Wing Chun is a landmark of action choreography and heroic womanhood in Chinese cinema. This book explores Wing Chun's narrative representation of femininity and the martial arts genre, its history, traditions and cultural influences.